SAT0355 Risk and Characteristics of Drug Induced Vasculitis in Patients Exposed to Tumour Necrosis Factor α Inhibitor Therapy: Results from the British Society for Rheumatology Biologics Register for Rheumatoid Arthritis. (9th June 2015) - Jani, M.; Dixon, W.; Kearsley-Fleet, L.; Bruce, I.; Chinoy, H.; Barton, A.; Lunt, M.; Symmons, D.; Hyrich, K.
Abstract : Background: Several reports have suggested an association between tumour necrosis factor inhibitor (TNFi) therapies and vasculitis as an immune mediated adverse event related to autoantibody formation; however, the incidence of this manifestation is unknown. Objectives: The aims of this study were to (i) compare the incidence of vasculitis in rheumatoid arthritis (RA) patients treated with TNFi to those receiving non-biologic drugs (nbDMARDs) and (ii) characterise these adverse events. Methods: The British Society for Rheumatology Biologics Register for RA (BSRBR-RA) is a prospective cohort study assessing the safety of biologic therapy. This analysis included two cohorts: (i) patients starting TNFi (adalimumab, etanercept, infliximab, certolizumab) as their first biologic (ii) a biologic-naïve comparison cohort receiving nbDMARDs. Patients were recruited to the study between 2001 and 2014. Additional information from consultants was sought for vasculitis episodes. Events were excluded in patients with (i) baseline systemic/nailfold vasculitis or (ii) receiving TNFi for RA vasculitis. Only patients who were biologic-naïve at baseline were included. The risk of an event was compared between the two cohorts using Cox proportional hazard models, adjusted using deciles of propensity scores. Events were attributed to TNFi therapy if they occurred within 90 days of being on drug. Follow-up was censored at first episode of vasculitis, switching to another biologic, death, last returned clinical follow-up or 31/05/2014, whichever came first. Results: There were 72 incident cases: 12 in 3673 nbDMARD patients and 60 in 12, 289 first TNFi-treated subjects generating crude incidence rates of 6/10, 000 and 12/10, 000 person years respectively (Table ). After adjusting for propensity score, the hazard ratio of vasculitis in patients on TNFi vs. nbDMARD was 1.13 (95% CI 0.51-2.49). The majority of cases were limited to cutaneous involvement (Table ). Other common systemic manifestations included digital infarction, neurological involvement and simultaneous arterial/venous thromboembolism (Table ). One patient in the TNFi cohort died after developing haemorrhagic alveolitis (leukocytoclastic vasculitis on lung biopsy) and bilateral episcleritis (cANCA, PR3+ve). Conclusions: In this large UK study, the incidence of TNFi induced vasculitis was not significantly higher compared with the nbDMARD treated comparator group after adjustment and the absolute risk in both groups was low. Cutaneous disease predominated in over half of the cases that occurred and TNFi induced systemic vasculitis was rare. Acknowledgements: MJ is a Medical Research Council Clinical Training Fellow supported by the North West England Medical Research Council Fellowship Scheme in Clinical Pharmacology and Therapeutics (funded by the Medical Research Council [grant number G1000417/94909], ICON, GlaxoSmithKline, AstraZeneca and the Medical Evaluation Unit). This abstract includes independent research supported by the National Institute for Health Research Biomedical Research Unit Funding Scheme. Disclosure of Interest: M. Jani Speakers bureau: Pfizer, W. Dixon: None declared, L. Kearsley-Fleet: None declared, I. Bruce Grant/research support from: GSK, Roche, Pfizer, UCB, Genzyme/Sanofi, H. Chinoy Grant/research support from: Novartis, Pfizer, Abbvie, Speakers bureau: Pfizer, Roche, MSD, Janssen, Abbvie, UCB, Servier, A. Barton Grant/research support from: Abbvie, Pfizer, Eli-Lilly and Sanofi-Aventis, M. Lunt: None declared, D. Symmons: None declared, K. Hyrich Grant/research support from: Pfizer, Speakers bureau: Abbvie